CEREBROVASCULAR DISEASES: THE POSSIBILITIES AND EFFICIENCY OF METABOLIC THERAPY - Kh. Ya. Umarova; A. Yu. Kazakov; A. V. Chugunov; M. M. Makeeva (Klinicist)
Acute and chronic brain ischemia is accompanied by complex metabolic rearrangements in the neurons. The ability of the cells to survive is largely determined by the presence of energy substrates and oxygen, the synthesis of neurotransmitters, and some other factors. The increasedpersistence of nerve tissue in ischemia and chances of recovering the impaired function can be achieved by the use of neuroprotective and neurotrophic agents. The efficiency of neurometabolic therapy is considered using Ceraxon and Actovegin as an example. It is emphasized that theefficiency of their administration can be achieved by the mandatory concurrent use of a wide range of nondrug treatments.